Characterization and pollution potential assessment of Tunceli, Turkey municipal solid waste open dumping site leachates - Demirbilek, Deniz; Onal, Ayten Oztufekci; Demir, Veysel; Uslu, Gulsad; Arslanoglu-Isik, Hilal (Springer, 2013)
Environmental monitoring of leachate quality from an open municipal solid waste dumping site in Tunceli, Turkey was studied in this research. The most commonly examined pollution parameters were determined on a seasonal basis. The annual average 5-day biological oxygen demand (BOD5) and chemical oxygen demand (COD) values of station points were measured as 70 and 425 mg/L, respectively, and also the average BOD5/COD ratio (a measure of biodegradability) was calculated as 0.20. The low ratio of biodegradability and slightly alkaline pH values in the leachate samples indicated that the site was characterized by methanogenic conditions. The mean ammonium-nitrogen (NH4 (+)-N) and corresponding phosphate (orthophosphate) values were assayed as 70 and 11 mg/L, respectively. The average solids content in the leachates was measured as 4,681 mg/L (total solids) and 144 mg/L (suspended solids). Very low concentrations of iron, manganese, copper, and zinc in the leachate samples were found and the concentration of cadmium was measured below detection limits. Excessive amount of nutrients and high organic and inorganic pollutant content in the leachates pose serious pollution potential to the environment. Since no drainage system or bio treatment exists in this open dumping site, high permeability of natural soil at the site and in the surrounding area and very fractured and crackled rocks under natural soil are indicators of high groundwater pollution potential in this site.
Keywords: Characterization; Leachate; Solid waste